Rapid 3D Bioprinting of Glioblastoma Model Mimicking Native Biophysical Heterogeneity. Issue 15 (27th January 2021) - Tang, Min; Tiwari, Shashi Kant; Agrawal, Kriti; Tan, Matthew; Dang, Jason; Tam, Trevor; Tian, Jing; Wan, Xueyi; Schimelman, Jacob; You, Shangting; Xia, Qinghui; Rana, Tariq M.; et al.
Abstract: Glioblastoma multiforme (GBM) is the most lethal primary brain tumor characterized by high cellular and molecular heterogeneity, hypervascularization, and innate drug resistance. Cellular components and extracellular matrix (ECM) are the two primary sources of heterogeneity in GBM. Here, biomimetic tri‐regional GBM models with tumor regions, acellular ECM regions, and an endothelial region with regional stiffnesses patterned corresponding to the GBM stroma, pathological or normal brain parenchyma, and brain capillaries, are developed. Patient‐derived GBM cells, human endothelial cells, and hyaluronic acid derivatives are used to generate a species‐matched and biochemically relevant microenvironment. This in vitro study demonstrates that biophysical cues are involved in various tumor cell behaviors and angiogenic potentials and promote different molecular subtypes of GBM. The stiff models are enriched in the mesenchymal subtype, exhibit diffuse invasion of tumor cells, and induce protruding angiogenesis and higher drug resistance to temozolomide. Meanwhile, the soft models demonstrate enrichment in the classical subtype and support expansive cell growth. The three‐dimensional bioprinting technology utilized in this study enables rapid, flexible, and reproducible patient‐specific GBM modeling with biophysical heterogeneity that can be employed by future studies as a tunable system to interrogate GBM disease mechanisms and screen drug compounds. Abstract : Biomimetic triregional glioblastoma multiforme (GBM) models are bioprinted with tumor regions, acellular extracellular matrix regions, and an endothelial region with regional stiffnesses patterned corresponding to the GBM stroma, pathological or normal brain parenchyma, and brain capillaries. Results show that biophysical cues are involved in various tumor cell behaviors and angiogenic potentials and promote different molecular subtypes of GBM.